Produk dari Priangan: Teh Rakyat di Priangan pada Awal Abad ke-20 - Syarah Nurul Fazri (Universitas Gadjah Mada, 2022)
This study discusses the development of People’s Tea cultivation that was intensified in Priangan in the early 20th century. Using historical methods, this study identified that local tea cultivation in the village served as an economic wheel, driving expansion and rotation within the community. The Plantations has become a magnet for the economy and opened up opportunities not only in the labor market but also attract businessmen around the plantations. The tea commodity was cultivated through European plantation companies and later expanded to the local resident’s land. The selling price tea worldwide in the early 20th century also stimulated the tea planters to participate in the business.